The Effect of Price, Service, and Complaints on Satisfaction in Perumda Giri Tirta Gresik - Riyanton, Riyanton; Suharto, Umar Burhan, (YUME : Journal of Management, 2025)
Clean water is an essential public service, and customer satisfaction with water utilities depends not only on access but also on how fairly and reliably that service is delivered. In Indonesia, where regional enterprises like Perumda Giri Tirta are tasked with managing local water distribution, public trust can be challenged by rising tariffs, inconsistent service, and slow complaint resolution. This study investigates the influence of price, service quality, and complaint handling on customer satisfaction using a quantitative explanatory approach with 100 respondents in Gresik Regency. Multiple linear regression results show that all three variables significantly affect satisfaction, with price as the most influential factor. Service quality and complaint handling also play important roles, especially for younger, educated users who demand greater transparency and responsiveness. The model accounts for 82.4% of the variation in satisfaction, emphasizing the need for clear communication, dependable service, and efficient complaint systems. These findings offer practical insights for improving the performance and public perception of local water utilities. Keywords: customer satisfaction, public utility, water service, tariff, complaint handling, regional enterprise.